Pengaruh Kompensasi terhadap Kinerja Karyawan pada PT. Parangloe Indah - Milen, Lusiana; Rasinan, Djusniati; Londong, Jerliyen P. (Lembaga Yasin AlSys, 2025)
This study aims to determine the effect of compensation on employee performance at PT. Parangloe Indah. Compensation is measured through bonus and motivation variables, while employee performance is measured based on the work achieved by the employee. The method used in this study is quantitative analysis with data collection techniques through questionnaires distributed to employees of PT. Parangloe Indah. The data obtained were then analyzed using the Pearson Product Moment correlation coefficient test, the determination coefficient test (r-Square), and the t-test to test the hypothesis proposed. The results showed that there was a significant positive relationship between compensation, especially in the form of bonuses, and employee performance. In addition, the results of the determination coefficient test showed that the motivation variable had a simultaneous influence on performance. Based on the results of the t-test, compensation has been proven to have a significant effect on employee performance at PT. Parangloe Indah. Thus, it can be concluded that increased compensation can contribute to improving employee performance.